(untitled) (World of finance, 2021)
Introduction. The functions of public expenditures reveal their intended purpose in the regulation of various processes and explain their role in the attainment of specific goals. Scientific literature provides extensive insights into definitions of budget functions in market democracies, but the functional purpose of public expenditures is covered only fragmentarily. The purpose of the article is to present a scientific substantiation for the system of public expenditure functions in the market democracies. Results. Based on the analysis of public expenditure functions, we believe that it would be feasible to substantiate the functions separately for each of the two main spheres directly affected by public expenditures, namely public management and the economic and social system of the country. In the public management sphere, public expenditures perform the functions of control and planning (programming). The essence of the planning function consists in using public expenditures to create conditions and provide necessary incentives for rational performance-based planning of the activities carried out by public authorities, as well as for attainment of target performance indicators by applying the results-oriented budgeting method. The function of control is preconditioned by the specifics of public management system functioning in a democratic society, which consists in assuring that the society has control over activities of public authorities. The influence of public expenditures on the national economy and its social system occurs through functions of allocation, redistribution and stimulation. The function of allocation consists in providing the population with goods and services that cannot be supplied by the market economy in sufficient volumes. The essence of the redistribution function consists in using public expenditures with the aim of decreasing income inequality among members of the society, regional development of territories or solving other tasks. The public expenditure function of stimulation aims to stimulate certain directions of economic activity by means of changing the volumes, components or structure of public expenditures through different mechanisms of their realization. Conclusions. In result of performing a theoretical study of the functional purpose of the budget in a market economy and a critical analysis of scientific postulates allow us to substantiate the feasibility of identifying the following functions of public expenditures: planning (programming), control, allocation, redistribution, and stimula tion.